The neurological effects of Glaucosciadium cordifolium (Boiss.) Burtt & Davis essential oil in a zebrafish model of cognitive impairment - Boiangiu, R. S.; Bagci, E.; Dumitru, G.; Hritcu, L.; Todirascu-Ciornea, E. (Wiley, 2023)
[Abstract Not Available]